2006
DOI: 10.1016/j.jaapos.2005.12.006
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Magnetic Resonance Imaging Demonstrates Abnormalities of Motor Nerves and Extraocular Muscles in Patients With Neuropathic Strabismus

Abstract: Introduction-Although the ocular motility examination has been used traditionally in the diagnosis of strabismus that is a result of cranial nerve (CN) abnormalities, magnetic resonance imaging (MRI) now permits the direct imaging of lesions in CN palsies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
70
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(71 citation statements)
references
References 10 publications
1
70
0
Order By: Relevance
“…4,6 High-resolution MRI has directly demonstrated cranial nerves and extraocular muscle pathology in several CCDDs and neuropathic strabismus. [7][8][9] In this report, we describe high-resolution MRI evidence suggesting peripheral cranial dysinnervation without brainstem dysplasia in three familial cases within the Möbius spectrum, having the rare clinical feature of complete ophthalmoplegia and bilateral facial diplegia.…”
Section: Introductionmentioning
confidence: 79%
“…4,6 High-resolution MRI has directly demonstrated cranial nerves and extraocular muscle pathology in several CCDDs and neuropathic strabismus. [7][8][9] In this report, we describe high-resolution MRI evidence suggesting peripheral cranial dysinnervation without brainstem dysplasia in three familial cases within the Möbius spectrum, having the rare clinical feature of complete ophthalmoplegia and bilateral facial diplegia.…”
Section: Introductionmentioning
confidence: 79%
“…In DRS, defects in horizontal eye movements result from incoordination of the medial and lateral recti muscles, which are innervated by the oculomotor and the abducens nerves, respectively (2). Neuroimaging studies suggest that DURS2 may involve absence of the abducens concomitant with aberrant innervation of the LR muscle by the OMN, and/or hypoplasia of both the abducens and oculomotor nerves (4,5). We have previously shown that expression of α2-chn forms harboring identified human mutations, in the oculomotor nerves of chicken embryos, leads to characteristic axon guidance defects, suggesting a role for α2-chn in axon pathfinding (3).…”
mentioning
confidence: 99%
“…72 Such changes included absence or hypoplasia of various oculo-motor nerves, hypoplasia and reduction in the size of the EOMs and even bony orbital changes. [73][74][75][76] Congenital fibrosis syndrome of the EOM Assaf 4,5 documented neurological findings in CFEOM patients using the CT and MRI scans. In his study of eight patients with CFEOM, in one case the CT-scan indicated agenesis of superior rectus in both eyes.…”
Section: Neural Imaging In Congenital Innervational Disordersmentioning
confidence: 99%